CHANGING ROLE OF LIBRARIANS IN 21ST CENTURY - Rameshwari (International Journal of Research -GRANTHAALAYAH, 2025)
The role of librarians has significantly evolved in the 21st century due to advancements in information and communication technology (ICT), the rise of digital libraries, and changing user expectations. Traditionally seen as custodians of books, librarians now serve as digital curators, educators, and technology specialists, facilitating access to vast online repositories and guiding users in digital literacy. Modern libraries function as community hubs, offering internet access, job training, and research support. The transition from physical to digital resources has necessitated new skills, including data management, AI integration, and cybersecurity awareness. Despite these advancements, challenges such as funding limitations, digital divides, and evolving technological landscapes persist. Libraries must continuously adapt by integrating emerging technologies and fostering collaboration among educators, researchers, and policymakers. The future of librarianship hinges on their ability to bridge knowledge gaps, ensure equitable access to information, and remain relevant in an increasingly digitized world. By embracing innovation, librarians will continue to serve as essential facilitators of learning and knowledge dissemination in the 21st century.